Pendidikan Matematika Realistik berbantuan Media Geogebra untuk Meningkatkan Hasil Belajar Geometri Ditinjau dari Kemampuan Spasial - Kadek Suryati; I Gede Adnyana (PendIPA Journal of Science Education, 2022)
The purpose of this research was to know the influence of the realistic mathematics education with geogebra media towards learning outcomes on geometry based on students’ spatial ability. This research s quasi experimental with experimental group 2x2 factorial research design. Sampling was taken random sampling technique. Before taking the sample, the student's ability equivalence test was conducted in each class using the one-way Anova The gathered data in this research are students’ spatial ability scores obtained from the spatial ability test and learning outcomes of geometry test. The collected data which after were analyzed using two way Anova. Before using two way Anova the data were analized for normality and homogeneity of variance. The results of this study are: (1) There are differences in geometry learning outcomes between students who follow the realistic mathematics education learning model assisted by geogebra media and the learning model commonly applied by teachers, namely the cooperative learning model, (2) There is an interaction of realistic mathematics education assisted by geogebra media with spatial abilities on geometry learning outcomes (Fcount of 5.937(p < 0.05)), this shows that the learning outcomes of geometry among students who attend realistic mathematics education assisted by geogebra media are better than students who take conventional learning in groups of students with spatial abilities.